2021
DOI: 10.5435/jaaos-d-21-00050
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Prolonged Duration of Symptoms on Mental Health in Anterior Cervical Disectomy and Fusion Patients

Abstract: Introduction: Prolonged duration of symptoms is associated with worse pain and disability in patients undergoing anterior cervical discectomy and fusion (ACDF). Our study aims to determine the effect of symptom duration on severity of depression among ACDF patients. Methods: We retrospectively reviewed a prospective surgical database from 2006 to 2019 for primary, single, or multilevel ACDF. Patients missing the duration of symptom information or patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…These differences fell below the KOOS JR minimum clinically important difference (MCID) of 6 [ 17 ]. VR-12 mental scores were equal between study and control cohorts for all collection intervals except at 1 year (54 vs. 56.4; p = 0.002), but this disparity similarly fell below an MCID of 6.5 [ 18 ]. VR-12 physical scores were equal between cohorts for all intervals except at 6 weeks (35.4 vs. 33.3; p = 0.005), with differences also falling below an MCID of 3 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences fell below the KOOS JR minimum clinically important difference (MCID) of 6 [ 17 ]. VR-12 mental scores were equal between study and control cohorts for all collection intervals except at 1 year (54 vs. 56.4; p = 0.002), but this disparity similarly fell below an MCID of 6.5 [ 18 ]. VR-12 physical scores were equal between cohorts for all intervals except at 6 weeks (35.4 vs. 33.3; p = 0.005), with differences also falling below an MCID of 3 [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Differences between KOOS JR scores again fell below an MCID of 6 [ 17 ]. An inverse effect was observed for ΔVR-12 mental ( – 2.4 vs. – 0.1; p = 0.01) and LEAS at 1 year (0.3 vs. 1.6; p < 0.001) (Table 5 ), with VR-12 differences falling below MCID [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Wichmann et al 16 found less postoperative satisfaction in patients with DOS > 3 months. Finally, Lynch et al 17 investigated mental health and largely found no difference in outcomes with longer DOS. Our data reported trends consistent with several of these prior publications.…”
Section: Discussionmentioning
confidence: 99%
“…In the lumbar radiculopathy literature, there is evidence to suggest that longer symptom duration is associated with worse health-related quality of life (HRQoL) measures. [6][7][8][9][10] For cervical radiculopathy, there is some evidence to suggest the same relation, [11][12][13][14][15][16][17] but the conclusions have been inconsistent. This long preoperative wait time in Canada presents a unique opportunity to analyze the impact of the preoperative duration of symptoms on HRQoL in patients with cervical radiculopathy.…”
mentioning
confidence: 99%